Floristic study and conservation value analysis of the Jordán river middle basin forest (Jujuy, Argentina) - Romeo, Raquel Ángela; Entrocassi, Gabriela Susana (Mediterranean Botany, 2020)
The floristic study and the conservation value analysis of forest from the Jordan river middle basin are addressed in this research. This vegetation forms part of the subtropical mountain forests or Yungas, one of the most diverse ecosystems on Earth. Present forest species were surveyed, and the vegetation Interest Conservation index (INCON) was determined based on a series of conservation value criteria (Phytocenotic, Territorial, Mesological, Ethnobotanical, Perceptual and Didactics) recorded in the field. Available data on socio-cultural aspects of the area was also included in the study. All plants were identified up to genera and/or species. INCON was calculated from the sum of scoring assigned to each analyzed criterion. As a result, 42 forest species were identified; for each one, its conservation status was performed, including the altitudinal vegetation belt, biogeographical origin (at least for the genus), and their ethnobotanical value. The INCON obtained (135 points) showed the high natural, ethnocultural, landscape, and educational value of these forest vegetation according to the criteria analyzed. This information provides a useful tool to have a more precise knowledge of the diversity conservation status of Las Yungas. It also serves to recognize the biological and environmental relevance of this area, whose usefulness can be used for conservation purposes or decision making on protection plans.